(untitled) (Universal International Scientific Journal, 2026)
The article analyzes the advantages of using digital platforms in teaching radiology and the innovations they introduce into the educational process. As a result of the development of information and communication technologies, the possibilities for effective organization of classes in higher medical education institutions are expanding. Through Moodle, Google Classroom, Microsoft Teams, Radiopaedia and PACS systems, students are provided with interactive educational materials, electronic textbooks, video lectures and virtual classes based on clinical cases. This process forms students’ independent thinking, clinical reasoning and analytical skills, and prepares them for practical work. There is also an opportunity to ensure the continuity and quality of the educational process using distance learning forms, automated assessment systems and simulation technologies. The results of the study show that classes taught using digital platforms provide higher learning outcomes than traditional methods. In conclusion, digital technologies play a significant role in increasing the efficiency of radiology education, developing modern diagnostic skills, and training competitive specialists.